Photogrammetric Survey for the Recording and Documentation of Historic Buildings - Stylianidis, Efstratios; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This book provides state-of-the-art information on photogrammetry for cultural heritage, exploring the problems and presenting solutions that are applicable under real-world conditions and in various disciplines. Allowing readers to gain a basic understanding of cultural heritage documentation and practical image-based modelling techniques, it focuses on the use of photogrammetry to enhance the documentation of historic buildings in order to reflect the international trends and meet demands of the preservation community. Addressing heritage documentation from various perspectives, the book will appeal students and researchers from engineering backgrounds as well as from the arts and humanities.
Introduction -- Terminology and international framework for documentation -- The need for documentation -- Historic buildings -- Planning: prior building surveying and documentation -- Measurements: introduction to photogrammetry -- Production: generating photogrammetric outcomes.
Keywords: Surveying; Cultural heritage; Remote sensing; Surveying; Cultural Heritage; Remote Sensing/Photogrammetry.